Investimento na função masculina em Biomphalaria tenagophila (ORBIGNY) (MOLLUSCA, PLANORBIDAE) avaliado pelo número de espermatozóides - MONTEIRO, WARTON (1998)
Biomphalaria tenagophila is a simultaneous hermaphrodite whose male function investment was estimated by counting spermatozoa from ovotestis and seminal vesicle, under different experimental conditions during the copulation process. As a new technique, spermatozoa were separated in a detergent solution. In all experimental conditions the seminal vesicle contained at least twice as many spermatozoa as the ovotestis to the order of a hundred thousand in ovotestis compared with three or four hundred thousands in the seminal vesicle. There is evidence that the spermatozoa transferred in the copulation process originate from the donnor's seminal vesicle, and the balance of the number of spermatozoa in the seminal vesicle was restored in less than 24 hours.